Glutathione redox cycle enzymes as potential targets for heme-mediated oxidation under hemolysis: in silico analysis - Barannik, T.; Ruzin, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
Glutathione (g-glutamylcysteinylglycine) redox homeostasis in human erythrocytes is dependent on the activities of glutathione peroxidase (GPX1, EC 1.11.1.9), glutathione reductase (GSR, EC 1.8.1.7), glutaredoxin 1 (GRX1) and NADPH-generating enzymes of pentose phosphate pathway, glucose-6-phosphate dehydrogenase (G6PD, EC 1.1.1.49) and 6-phosphogluconate dehydrogenase (PGD, EC 1.1.1.44). Free heme accumulation under hemolysis can affect proteins activity thereby in silico analysis of glutathione redox cycle enzymes structure was performed in order to reveal putative heme-binding sites and oxidizable cysteine residues. Protein annotations were taken from UniProt. Heme docking was performed by PatchDock with clustering RMSD 1,5 Å using PDB structures of proteins and heme. Cysteines oxidation potential was estimated by Cy-Preds. Heme binding GSR monomers (1DNC, 3DJJ, 3DK9, 2GRT) and dimers (3SQP, 2GH5) was predicted through His81 close to interchain disulfide bond and through Cys59 near FAD and GSSG binding sites. Heme-binding areas in GPX1 (2F8A) and GPX3 (2R37) also were revealed in the interchain region and in active centre (His80). GLRX1 (4RQR) was predicted to bind heme almost exclusively near the N-end in spite of accessibility of all cysteines including CPYC motif in active centre. G6PD monomer (2BH9, 5UKW) revealed heme-docking areas in NADP+ binding region and a-helix 437–447 located in dimer 2BHL at the interchain surface. Heme docking to PGD (4GWG, 4GWK) was in substrate binding region near His187. So enzymes active centres and chain interaction regions were revealed in the most of heme docking variants. From one (in PGD) to three (GSR) cysteines susceptible to oxidation were found in each protein including cysteines that were predicted to bind heme. Heme-mediated oxidative effect on glutathione redox cycle enzymes in erythrocytes and blood plasma could be an important mechanism of hemolysis progression under stress and pathologies.